2020
DOI: 10.1017/s0025315420000867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow velocity on fitness-related behaviours of the sea urchin Mesocentrotus nudus: new information on stock enhancement

Abstract: The effects of flow velocity on the fitness-related behaviours of Mesocentrotus nudus remain largely unknown, greatly hampering the efficiency of stock enhancement. To explore the appropriate velocities for stock enhancement, we investigated dislodgement and immobilization velocities up to 90 cm s−1. The experimental results showed that M. nudus (test diameter of ~30 mm) were dislodged at 73.50 ± 7.7 cm s−1 and that M. nudus movement occurred only when the flow velocity was less than 33.40 ± 2.7 cm s−1. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…For example, it greatly increases the energy consumption of the fish Rhynchocypris lagowskii 34 and reduces the fat content of the flounder Paralichthys olivaceus 35 . Consistently, our previous studies found that high flow velocity displays negative effects on the growth and development of sea urchins 18 , 28 . Here, we further found three metabolism pathways through KEGG analysis, including arachidonic acid metabolism, linoleic acid metabolism, and arginine and proline metabolism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, it greatly increases the energy consumption of the fish Rhynchocypris lagowskii 34 and reduces the fat content of the flounder Paralichthys olivaceus 35 . Consistently, our previous studies found that high flow velocity displays negative effects on the growth and development of sea urchins 18 , 28 . Here, we further found three metabolism pathways through KEGG analysis, including arachidonic acid metabolism, linoleic acid metabolism, and arginine and proline metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study found that test diameter and body weight of M . nudus increased significantly slower at a high flow velocity 18 . Tube feet of sea urchins are highly sensory 19 .…”
Section: Introductionmentioning
confidence: 88%